Nghiên cứu tính chất và cấu trúc vật liệu HDPE/bột gỗ gia cường bởi hạt nano titan dioxyt có sử dụng chất tương hợp PEGMA - Huynh, Mai Đức; Hoàng, Thái; Giang, Nguyễn Vũ; Trung, Trần Hữu (Vietnam Journal of Chemistry, 2014)
In this research, the polymer composites based on high density polyethylene (HDPE) resin and wood flour using the PEgMA compatibilizer and rutile titanium dioxide (TiO2) nanoparticles were prepared by melt-mixing method in a Haake internal mixer. In the presence of 4 wt.% of the compatibilizer and 1 wt.% of modifies TiO2 nanoparticles in the compositions of the HDPE/WF composite (with 50 wt.% of wood flours) increased the tensile strength up to a highest value of 32.51 MPa. The structural morphology was studied by using a field emission scanning electron microscopy (FE-SEM) clearly indicated the leading roles of compatibilizer and inorganic nanoparticles contributing to the enhancement of the flexural strength and minimizing the soak of the composite material as well. The addition a small content of (1 wt.%) TiO2 nanoparticles increased significantly the melting viscosity of composite mixture, therefore, assisting the processibility of pressing-extrusion technique. Keywords: HDPE, TiO2, wood flour, wood – thermoplastic composite, processibility.